Hybird fiber reinforced concrete: steel and coconut coir - Shamir , Sharafaddin (2013)
Hybrid fiber reinforced concrete can be defined as concrete that reinforced by two or more types of fibers. This study aims to study the mechanical properties of hybrid fiber reinforced concrete where the fibers used were consists of steel fiber and coconut coir fiber. For this purpose six mixes, one normal control mix and five hybrid fiber reinforced concrete mixes were prepared. The total content of two fibers is 3% by volume of mix where the total content of each fiber varied from 0.5% to 2.5%. Slump Test and Compaction Factor Test was carried out for each mix in the fresh state in order to determine the workability of the hybrid fiber reinforced concrete. Meanwhile, compressive test and flexural test were carried out to study the mechanical properties of the hybrid fiber reinforced concrete. From the slump test and compaction factor test, all specimens show low workability except the samples which contain more steel fibers than coir fibers. These two mixtures of samples give results of very low workability. For the result of Compressive and Flexural Test, the normal control mix shows normal strength development but all the hybrid fiber reinforced concrete mixes gain their strength lower the normal control mix. The expected outcome which is the strength of hybrid fiber reinforced concrete is higher than the strength of normal concrete did not achieved. So, further research need to be carried out with some adjustments of methods or materials.